Evidence for ca. 2046 Ma high-grade metamorphism in Paleoproterozoic metasedimentary rocks of the northern Borborema Province, NE Brazil: constraints from U-Pb (LA-ICP-MS) zircon ages - Bruno de Oliveira Calado; Felipe Grandjean Costa; Iaponira Paiva Gomes; Joseneusa Brilhante Rodrigues (Journal of the Geological Survey of Brazil, 2019)
This study presents LA-ICP-MS U-Pb detrital zircon ages on a migmatitic paragneiss of the Jaguaretama Complex, northern Borborema Province, NE-Brazil. This metasedimentary rock comprises a stromatic migmatite with alternating layers of metapelite, metapsammite, and garnet-tourmaline-bearing leucosome. The paleosome displays a well-developed schistosity, with fine to medium-grained textures, and locally garnet porphyroblasts. Backscattered electron images show that many of the zircon grains display metamorphic overgrowths (recrystallization) and cores with igneous oscillatory zoning. The detrital zircon grains show 207Pb/206Pb ages clustering from 2.51 to 2.12 Ga (with 90% conc.), evidencing that the igneous sources were generated mostly during the Transamazonian/Eburnean orogeny. The age of 2137±9 Ma of the youngest and most concordant detrital zircon (core) is interpreted as the maximum depositional age of the protolith. The youngest and most concordant (conc. 99%) 207Pb/206Pb apparent age obtained in a metamorphic zircon overgrowth was 2046±6 Ma, which is interpreted as the age of high-grade metamorphism. This age of metamorphism is similar to other records of Paleoproterozoic high-grade metamorphic events in the Borborema Province and other cratonic domains (e.g. São Francisco and West Africa cratons). This age also represents the minimum depositional age of the protolith. Therefore, the depositional age of the studied supracrustal rock may be bracketed between ca. 2.14 and 2.05 Ga.